Application of Mufrodat Quiz Game Media to Improve Vocabulary Mastery of Grade VIII Students of the Medan IRA College Foundation - Putra Putra; Zulfahmi Lubis; Akmal Walad Ahkas (EduInovasi: Journal of Basic Educational Studies, 2023)
This study's objective is to provide students with solutions to problems that must be addressed when learning Arabic, namely: 1) When learning Arabic, why do students at MTs Class VIII IRA Medan College Foundation experience boredom and sleepiness? is going on? 2) When learning Arabic, how do students at MTs Class VIII IRA Medan College Foundation feel engaged and happy? 3) Is it possible for the Application of Mufrodat (Vocabulary) Quiz Game Media to engage students and enhance their Arabic vocabulary mastery? Therefore, the researcher intends to use the Mufrodat (Vocabulary) Media Quiz Game to increase students' active participation in Arabic learning and mastery of mufrodat (vocabulary). Classroom Action Research, or CAR, is the method that researchers employ. Students in Class VIII as research subjects. Observation and practice questions were used for data collection. Descriptive qualitative and quantitative data analysis was used. This study was carried out in two stages by researchers, and each stage required two meetings. The first meeting took place on January 19, 2023, and the second meeting took place on January 20. The researcher used the mufrodat quiz game media on class VIII students in stage I (meetings I and 2), and the results showed an increase in learning activity and student learning values. This is demonstrated by the number of students who increased their KKM scores at the first meeting, which was six students, and by the number of students who completed the KKM scores of the 21 students who participated in the practice questions, which did not meet the specified Minimum Completeness Criteria. i.e. 85 percent and must be increased. The researcher carried out phase II to address the flaws discovered in stage I. At this stage, the research was also carried out in two meetings, on February 9 and February 10, 2023. Meetings I and 2 demonstrated a significant rise in stage II. This is demonstrated by the fact that the number of students who achieved the KKM score increased from 10 students in the first stage to 14 students in stage II of the first meeting. In the second meeting, the number of students who achieved individual completeness scores or the minimum completeness of 21 students who participated in the practice questions increased to 18 students. In other words, the mufrodat mastery (vocabulary) results have improved as a result of using the mufrodat quiz game media because they met the study's Minimum Mastery Criteria.. Keywords: Media Quiz Game Mufrodat; Penguasaan Mufrodat (Kosakata); Peserta Didik